WHAT DRIVES USERS OF FINANCIAL TECHNOLOGY TO DONATE DURING THE EARLY STAGE OF PANDEMIC? - Kartika, Tika; Ahmad, Abdul Razaq; Hakim, Nurman (Al-Infaq: Jurnal Ekonomi Islam, 2022)
The COVID-19 pandemic has triggered people to make massive use of fintech. This fintech adoption increases the level of Islamic financial literacy. Fintech-based social finance services are no exception. This study aims to capture the initial development of the use of fintech for philanthropic purposes by using a qualitative-descriptive method with a literature study and content analysis approach. The results of the study show that within the time the article was published, there was a gradual increase in user awareness of the need to adopt fintech. Before the time of the pandemic, awareness of fintech adoption remained low. After 2019, based on historical studies and its evolution in Islamic fund management, it is predicted that fintech will have great potential going forward. The profile of fintech service users will increase in the baby-boomer generation. Generation X and Z consumers will play a significant role in the global economy, while the millennial generation is bringing major changes to the behavioural demographics and user expectations for fintech services. Moreover, fintech services emerged in Indonesia using the Agricultural Value Chain Financing (AVCF) approach, namely a platform that improves agricultural-based product services for consumers and provides more flexible financial assistance for AVCF players. On the social finance side, almost all of the respondents knew about fintech, and they agreed that fintech offers a lot of conveniences and benefits. Fintech increases the intention of Muslim millennials to donate easily, even though not all agree and are comfortable using fintech to donate. In 2020, the phenomenon of Islamic Fintech emerged, and it was found that perceptions of benefits and convenience, behavioural intentions, as well as trust, are determinants of using fintech for philanthropic purposes.